Glitch art: uma estética do erro - Livia Chagas Feliciano (2018)
This dissertation analyzes the aesthetics of digital error, called by some artists and theorists as Glitch art, through three main axes. The first one analyzes the concepts that accompany the theme, such as error, chaos and chance, with special attention to the view of the theorists Friedrich Nietzsche and Gilles Deleuze. The second examines the aesthetic characteristics of the works and the most relevant artists working with visual, sonorous and audiovisual error and the third axis demonstrates some practical possibilities of glitch production.